Electromagnetic therapy for treating venous leg ulcers - Aziz, Zoriah; Cullum, Nicky (Cochrane Collaboration, 2015)
Background Leg ulceration is a common, chronic, recurring condition. The estimated prevalence of leg ulcers in the UK population is 1.5 to 3 per 1000. Venous ulcers (also called stasis or varicose ulcers) comprise 80% to 85% of all leg ulcers. Electromagnetic therapy (EMT) is sometimes used as a treatment to assist the healing of chronic wounds such as venous leg ulcers.